Pricing Strategies of Registration System and Transaction System in Live Broadcast Platform - Rong Zhang; Ying Xu; Bin Liu (Discrete Dynamics in Nature and Society)
This paper investigates a supply chain consisting of the monopoly live broadcast platform, content producers, and consumers. Based on the two-sided market theory, the platform’s pricing strategies and their analysis are considered under the registration system and the transaction system. Firstly, it shows that platform users’ scale and profit are positively correlated with the intergroup network externality from both sides and the intragroup network externality inside the consumer group and negatively correlated with the intragroup network externality inside the content producer group. Secondly, the platform profit, registration fee charged to content producers, and transaction fee charged to consumers are negatively correlated to the content production cost and positively related to consumers’ content quality sensitivity coefficient. When consumers are more sensitive to content quality, they are positively correlated to content quality. Finally, the registration fee charged by the platform to consumers is positively correlated with the content production cost, negatively correlated with the content quality level, and positively associated with the consumer content quality sensitivity coefficient.